Understanding Layered Double Hydroxide properties as sorbent materials for removing organic pollutants from environmental waters. Issue 4 (August 2021) - Johnston, Amy-Louise; Lester, Edward; Williams, Orla; Gomes, Rachel L.
Abstract: Emerging contaminants (ECs) are a group of anthropogenic organic pollutants known to have a host of adverse environmental and health implications. The removal of such pollutants from aqueous environments to ensure water is of a quality fit for reuse is therefore highly important and gaining considerable interest. Whilst there are multiple approaches used for EC remediation from water matrices, sorption using layered double hydroxides (LDHs) has been reported as a suitable technique. LDHs are interesting clay-like materials with numerous properties which lend LDHs to being suitable sorbent materials. Such properties include low toxicity, anion exchange capacity and tuneable structures through possible variations in metals, anions and preparation techniques. To design a successful sorbent material, it is important to fully understand the materials structure-property-function relationship. However, in the application of LDHs as sorbent materials for the removal of organic pollutants, this relationship is not well understood. Hence the ability to design bespoke high-performing LDH sorbent material is currently limited. This review considers the impact of structure and related physiochemical properties of LDHs on their sorption capacity for the removal of organic pollutants from water matrices. Methyl Orange (MO) is first considered as a model pollutant, with the importance of the characteristics of the metal layers, interlayer anions and resulting textual properties of LDHs on reported sorption capacity observed. A comparison is then made between the findings from the MO case study and for the sorption of other organic pollutants using LDHs, with a particular focus on pharmaceuticals. Finally, the role of environmental conditions and considerations linked to possible commercial applications are discussed, with recommendations made for future work. Graphical Abstract: ga1 Highlights: LDH properties impacting sorption capacity broadly similar for organic pollutants. Sorption is described by the Langmuir isotherm and pseudo-second order kinetics. Anion exchange is a key mechanism for high sorption capacity of LDHs. Synergistic sorption mechanisms result in complex ideal LDH properties. Environmental conditions play a significant role in sorption processes using LDHs.